Short Communication: Effect of growing media on seed germination and seedling growth of Aganope heptaphylla (Leguminosae) - R. SUBEKTI PURWANTORO (Nusantara Bioscience, 2016)
Abstract. Purwantoro RS. 2016. Effect of growing media on seed germination and seedling growth of Aganope heptaphylla (Leguminosae). Nusantara Bioscience 8: 150-154. This study was carried out to explore the effect of growing media on seed germination and seedling growth of Aganope heptaphylla (L.) Polhill. The research was conducted in the greenhouse of Bogor Botanic Gardens nursery for two months from July to August in 2015. An experiment was carried out employing a completely randomized design with three treatments and three replications. The treatments were different sowing media: sand, rice husks, and sawdust. Each treatment had 15 seeds placed in plastic trays. The results showed that the germination percentage in the rice husk medium (75.6%) was higher and the peak germination value (0.55) significantly higher (at p<0.5) than in the other media. The medium of rice husks was found to be significantly best for the growth of the seedlings; it gave the highest growth in terms of seedling height (40.5 cm), number of roots (46) and the length of roots (11.2 cm).